Manajemen Sumber Daya Manusia Dalam Meningkatkan Kompetensi dan Kinerja Guru di Madrasah Ibtidaiyah Wajib Belajar Desa Pekukuhan Kecamatan Mojosari Kabupaten Mojokerto - M, Mulyono; Sembodo, Sigit Priyo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes the application of Human Resource Management (HRM) in improving the ability and performance of teachers in Compulsory Primary Schools in Pekukuhan Village, Mojosari District, Mojokerto County. The background of the study shows that although these madrasahs have limitations in budget, training, and facilities, the principals have a key role in managing human resources in a participatory and context-appropriate manner. The study used a qualitative method with a case study. Data were collected through observation, in-depth interviews with madrasah principals and the teachers, as well as documentation. The data obtained was descriptively analyzed to identify human resource management practices, supportive and hindering factors, as well as the leadership role of madrasah principals. The results of the study indicate that human resource management in these madrasas is applied in a flexible manner, with a focus on informal development, internal training, and reinforcement of religious values. Supporting factors were mainly the leadership of the principal who was easily invited to communicate and a familiar work culture among the staff. However, there are several major barriers, including lack of funding, limited access to technology, and there is not yet a ready-made performance evaluation system. Even so, this context-appropriate human resource management approach proved to be effective in improving teachers’ motivation and performance, suggesting that humane and adaptable leadership is capable of overcoming structural disadvantages. This study underlines the importance of sensitive leadership and the development of a supportive work culture in human resource development in educational environments with limited resources.